Le De quantitate animae d'Augustin, un dialogue philosophique ? - Lagouanère, Jérôme (Zeitschrift für antikes Christentum, 2019)
Saint Augustine's De quantitate animae is a dialogue often neglected by scholars who have studied the question of Augustinian dialogue. This study aims to remedy this lack of interest and to show the strategic place of this dialogue in the Augustinian production of the years 386-390. Firstly, after stating the question, the article questions the genre of dialogue and shows that the De quantitate animae of Augustine perfectly meets the criteria defining the genre of the philosophical dialogue. Secondly, this study examines the stakes and the place of the dialectic in this work. In fact, our paper emphasizes, following the analyzes proposed by Giovanni Catapano, the importance of considering the kind of dialogue in Augustine by the yardstick of his epistemological presuppositions. In this perspective, the De quantitate animae appears as a work of transition, which is based on the epistemology of Contra Academicos and the notions of doubt and inconcussum, while announcing the epistemology of the inner Master developed in the De magistro.